HUBUNGAN TINGKAT KONTROL ASMA DAN KUALITAS HIDUP PENDERITA ASMA YANG BEROBAT DI RSUD DOKTER SOEDARSO PONTIANAK PADA BULAN MARET SAMPAI DENGAN MEI TAHUN 2012 - ., Rahayu (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background. The goals for asthma management are to achieve andmaintain controlled asthma, so that patient with asthma can live normally.The relation between asthma control level and quality of life in asthmapatients treated at dr. Soedarso general hospital Pontianak has not beeninvestigated.Objective. The aim of this study was to assess the relation between asthmacontrol level and quality of life in asthma patients treated at dr. Soedarsogeneral hospital Pontianak.Methods. This study was a cross sectional analytic study. This study wasconducted at dr. Soedarso general hospital Pontianak from March until Mei2012. Data was collected from 100 asthma patients who visited theoutpatient clinic and inpatient unit of lung disease at dr. Soedarso generalhospital Pontianak using Asthma Control Test(ACT)and StandardizedAsthma Quality of Life Questionnaire(AQLQ-S). Data was analyzed withChi-square test.Results. All asthma patients with poor quality of life have uncontrolledasthma, asthma patients with moderate quality of life more often haveuncontrolled asthma than controlled asthma, and all asthma patients withgood quality of life have controlled asthma. There were significant relation(p=0,000)between asthma control level and quality of life.Conclusion. Asthma control level influenced quality of life in asthmapatients treated at dr. Soedarso general hospital Pontianak from March untilMay 2012.Keywords : asthma control level, quality of life, asthma control test,standardized asthma quality of life questionnaire